2022
DOI: 10.1038/s41598-022-10133-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of FDA-approved drugs identified by cluster analysis of behavioral profiles

Abstract: Repurposing FDA-approved drugs is an efficient and cost-effective approach in the development of therapeutics for a broad range of diseases. However, prediction of function can be challenging, especially in the brain. We screened a small-molecule library with FDA-approved drugs for effects on behavior. The studies were carried out using zebrafish larvae, imaged in a 384-well format. We found that various drugs affect activity, habituation, startle responses, excitability, and optomotor responses. The changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Other laboratories have previously shown that zebrafish larvae initially startle in response to sound pulses with a 1‐s interval, but quickly habituate to such stimuli (Best et al., 2008; Wolman et al., 2011). Subsequent studies in our own laboratory showed that habituation to sound stimuli with a 1‐s interval can be measured in a 384‐well format (Tucker Edmister, Del Rosario Hernandez, et al., 2022; Tucker Edmister, Ibrahim, et al., 2022). CsA and FK506 were used to suppress calcineurin signaling, proINDY was used to activate calcineurin signaling, and cotreatments were carried out to examine if proINDY is an effective therapeutic to restore calcineurin signaling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other laboratories have previously shown that zebrafish larvae initially startle in response to sound pulses with a 1‐s interval, but quickly habituate to such stimuli (Best et al., 2008; Wolman et al., 2011). Subsequent studies in our own laboratory showed that habituation to sound stimuli with a 1‐s interval can be measured in a 384‐well format (Tucker Edmister, Del Rosario Hernandez, et al., 2022; Tucker Edmister, Ibrahim, et al., 2022). CsA and FK506 were used to suppress calcineurin signaling, proINDY was used to activate calcineurin signaling, and cotreatments were carried out to examine if proINDY is an effective therapeutic to restore calcineurin signaling.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that acute CsA and FK506 treatments induce hyperactivity in response to acoustic stimuli with a 1‐s interval, a behavior that we refer to as excitability (Tucker Edmister, Del Rosario Hernandez, et al., 2022; Tucker Edmister, Ibrahim, et al., 2022). In the present study, we examined effects of developmental exposures on excitability (Figure 4(c)).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations